Internal Audit, Strategic Risks and Corporate Financial Distress - Al-sagheer , Nabaa Hussein Abdulzhraa; BACHA , Sami (Journal of Ecohumanism, 2024)
This study shed lights on the effect of internal audit effectiveness on firm’s exposure to financial distress. Specially, we examine whether the adoption of strategic audit may enhance the internal audit effectiveness, thus reducing the risk of default. Using a quantitative research framework, through the administration of a survey to 109 Iraqi internal auditors working in public and private companies based in Najaf governorate, the results show that the adoption of strategic audit leads auditors overcoming both operational and strategic risks, improving thus the corporate performance. The identification of strategic risks and threats by internal auditors significantly reduces the cases of financial default. The findings also reveal that the strategic audit may help auditors to anticipate crisis and enhance the firms’ resilience to shocks. This study has practical and managerial contributions. It encourages internal auditors to extend their abilities and competencies to overcome both operational and strategic risks. They should consider the effect of external risks on corporate performance when developing audit programs and controlling for managerial failures.